Symbiotic, low-temperature, and scalable synthesis of bi-magnetic complex oxide nanocomposites. Issue 2 (22nd January 2020) - Sayed, F.; Kotnana, G.; Muscas, G.; Locardi, F.; Comite, A.; Varvaro, G.; Peddis, D.; Barucca, G.; Mathieu, R.; Sarkar, T.
Abstract : Low-temperature, symbiotic synthesis of nanocomposites, with heat of formation of phase1 crystallizing phase2, and phase2 preventing grain growth of phase1. Abstract : Functional oxide nanocomposites, where the individual components belong to the family of strongly correlated electron oxides, are an important class of materials, with potential applications in several areas such as spintronics and energy devices. For these materials to be technologically relevant, it is essential to design low-cost and scalable synthesis techniques. In this work, we report a low-temperature and scalable synthesis of prototypical bi-magnetic LaFeO3 –CoFe2 O4 nanocomposites using a unique sol-based synthesis route, where both the phases of the nanocomposite are formed during the same time. In this bottom-up approach, the heat of formation of one phase (CoFe2 O4 ) allows the crystallization of the second phase (LaFeO3 ), and completely eliminates the need for conventional high-temperature annealing. A symbiotic effect is observed, as the second phase reduces grain growth of the first phase, thus yielding samples with lower particle sizes. Through thermogravimetric, structural, and morphological studies, we have confirmed the reaction mechanism. The magnetic properties of the bi-magnetic nanocomposites are studied, and reveal a distinct effect of the synthesis conditions on the coercivity of the particles. Our work presents a basic concept of significantly reducing the synthesis temperature of bi-phasic nanocomposites (and thus also the synthesis cost) by using one phase as nucleation sites for the second one, as well as using the heat of formation of one phase to crystallize the other.